KAJIAN EKSISTENSI KEARIFAN LOKAL MASYARAKAT DESA ADAT TENGANAN PEGRINGSINGAN DALAM PENGELOLAAN HUTAN DI DESA TENGANAN, KECAMATAN MANGGIS, KABUPATEN KARANGASEM, PROVINSI BALI - , MADE PUTRI KARIDEWI, SST.PAR.; , Dr. Su Ritohardoyo, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
For the customary community at the customary village of Tenganan Pegringsingan, the existence of local wisdom in form of customary law or âawigawigâ is playing an important role in local forest management. Itâs been proved by a well-maintained forest condition which has successfully preserved until these days. Problems are arised when the existence of âawig-awigâ which was inherited since 11th century is not only determine by an acknowledgement from the customary community itself but also by some internal and external factors surrond âawig-awigâ in doing its functions. The aim of this research are to study how far the effectiveness of local wisdom has been carried out as well as several factors which had an affect on the level of effectiveness of local wisdom implementation in forest management over a site. More further, the aim is to discover some concepts of community perception toward the effectiveness of local wisdom. Those concepts become a basis to develop a local wisdom-based forest management strategy. This research was used a qualitative method with data collection mostly through in-depth interview and observation, in addition to secondary data interpretation as a complement. Samples were selected using a purposive sampling technique. Data were analyzed inductively using a categorization method. Review of data credibility or data trustworthiness using a triangulationsource technique. The result of this research shows that the effectiveness of local wisdom implementation in general is still going fairly effective although the substance of each clause has its own weaknesses. The devotion of customary community to the customary law is still fairly high and the violation of the law has not signify effected the forest condition. The community perception was resulting four concepts of perception which one each other has an interrelationship. Those concepts are âawig-awigâ flexibility, âawig-awigâ implementation mechanism, community participation, and the sustainability of forest functions. All internal and external factors that had an affect on the level of effectiveness of local wisdom implementation were resulting four effectiveness criteria which are âawig-awigâ substance, forest management method, people involved, and âawigawigâ implementation mechanism. The development of forest management strategies based on the existing local wisdom are addressed to improve the traditional management system in order to assist the customary community to carry out all tasks related to forest management effectively.